Unpacking Settler Colonialism’s Urban Strategies: Indigenous Peoples in Victoria, British Columbia, and the Transition to a Settler-Colonial City - Edmonds, Penelope (Urban History Review / Revue d'histoire urbaine)

(untitled) (Urban History Review / Revue d'histoire urbaine, 2010)
This article uses settler colonialism as a specific analytic frame through which to understand the historical forces in the formation of settler cities as urbanizing polities. Arguing that we must pay attention to the intertwined histories of immigration and colonization, the author traces the symbolic and economic functions and origins of the settler-colonial city to reveal its political imperatives, the expropriation of Indigenous land, and the dispossession, removal, sequestration, and transformation of Indigenous peoples. Taking as a case study the city of Victoria, BC, and its Lekwungen people throughout the nineteenth century, the author charts the shift from a mixed and fluid mercantilist society to an increasingly racialized and segregated settler-colonial polity. This transition reveals how bodies and urbanizing spaces are reordered and remade, and how Indigenous peoples come to be produced and marked by political categories borne of the racialized practices of an urbanizing settler colonialism, which complement the powerful forces of settler ethnogenesis and colonial modernity.